The role of ROS-induced pyroptosis in CVD - Tian, Kaijiang; Yang, Yu; Zhou, Kun; Deng, Nianhua; Tian, Zhen; Wu, Zefan; Liu, Xiyan; Zhang, Fan; Jiang, Zhisheng (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular disease (CVD) is the number one cause of death in the world and seriously threatens human health. Pyroptosis is a new type of cell death discovered in recent years. Several studies have revealed that ROS-induced pyroptosis plays a key role in CVD. However, the signaling pathway ROS-induced pyroptosis has yet to be fully understood. This article reviews the specific mechanism of ROS-mediated pyroptosis in vascular endothelial cells, macrophages, and cardiomyocytes. Current evidence shows that ROS-mediated pyroptosis is a new target for the prevention and treatment of cardiovascular diseases such as atherosclerosis (AS), myocardial ischemia-reperfusion injury (MIRI), and heart failure (HF).